Rainfed Farming Systems of Hyper Arid North-Western Rajasthan: An Analysis - Rathore, V S; Singh, J P; Beniwal, R K (Annals of Arid Zone, 2016)
Three micro-farming situations (MFS’s) were identified in rainfed area of district Bikaner. The identified MFS’s varied considerably with respect to socio-economicconditions, composition of crops and livestock, productivity, economics and constraints associated with crop and dairy animal components of existing farming systems. Among the crops clusterbean either grown as sole or mixed crop had maximum area followed by pearl millet+moth bean mixed crop. Clusterbean+sesame, sole clusterbean and chickpea were most remunerative crops in MFS-I,II, and III, respectively. Highest milk prodllctivity was registered in MFS-III followed by MFS-I and II. Pest incidences, lack of improved seeds, less remunerative prices, lack of improved tech-know-how were major constraints in crop production, and their relative ignificancewere crop and micro farming situation specific. Scarcity of fodder emerged as major constraint in milk production in all MFS’s. Key words: Hyper arid, micro farming situation, crop, dairy animal, productivity, economics, constraints.